The place of ganglion or root alcohol injection in trigeminal neuralgia. - Sharr, M M (1977)
Of 157 patients with trigeminal neuralgia, referred for neurosurgery, 81 underwent 85 ganglion or root injections. The results, which are analysed with regard to pain relief and sensory loss, compare favourably with results from the literature of other forms of surgery, particularly open temporal root section.